(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Renal failure is defined as the kidney's inability to execute excretory activities, resulting in the retention of nitrogenous wastes in the blood. Renal insufficiency patients are more susceptible to infections because the host's immune system is compromised. As a result, CKD patients are more likely to develop an infection that leads to bacteremia and sepsis. This study involved 130 CKD patients with infections who participated in a prospective observational study. E.Coli and Klebsiella pneumonia were the most common microbes found in the study, followed by Pseudomonas aeruginosa, Coagulase negative staphylococci, Acinetobacter baumannii, Nonfermenting Bacilli, Streptococci, and Enterococcus faecalis. E.Coli and Klebsiella pneumonia were the bacteria with the highest incidence of causing infections in CKD patients. Resistance to Levofloxacin, Doxycycline, and Cefpodoxmine Proxetil was identified in E.Coli. Resistance to Piperacillin with Tazobactam, Levofloxacin, Doxycycline, and Cefpodoxmine Proxetil were also found in Klebsiella pneumoniae. To resolve the condition, proper diagnosis and therapy are required. This is an issue that all health care practitioners, particularly clinical pharmacists, should pay more attention towards.